High Achieving First-Generation University Students - Nikki Shure; Larissa Zierow (Center for Economic Studies and ifo Institute (CESifo), 2023)
First-generation university graduates have been found to face a series of disadvantages on their pathway to higher education and the labor market. We use unique, national level data on high achieving university graduates to attempt to disentangle the importance of lower prior attainment from parental educational background on a series of higher education and labor market outcomes. We compare first-generation and non-first-generation graduates who are recipients of a prestigious national scholarship program targeted at the top percentile of the student distribution in Germany. We find the first-generation high achievers are more likely to study at less prestigious institutions and at institutions that are closer to home even though they have the prior attainment to go further afield. They are also less likely to study subjects with high labor market returns and are more likely to work in jobs with high job security. We furthermore find evidence that especially female first-generation high achievers are less likely to see the value of the networking opportunities the scholarship provides.
Keywords: I24; J24; 330; socio-economic gaps; first-generation; higher education